Experimental investigation of the effect of cross wire on the flow field of elliptic jet - Faheem, Mohammed; Khan, Aqib; Kumar, Rakesh; Khan, Sher Afghan; Asrar, Waqar; Sapardi, Mohd Azan Mohammed (Elsevier, 2021)
The effectiveness of cross wire in controlling the mixing characteristics of a circular and an equivalent elliptic jet is investigated experimentally. While circular jets are conventional, elliptic jets have gained attention due to their better mixing characteristics and faster decay. To further explore and augment the capabilities of elliptic jets for practical utility, it is investigated whether using an elliptic jet with cross wire control gives additional benefit in terms of mixing enhancement over an axisymmetric jet. Experiments are performed for subsonic and choked flow conditions with nozzle pressure ratios ranging from 1.2 to 7.0. Time-averaged pitot pressures and schlieren visualization is used for diagnosis. The jet bifurcation can be seen in controlled elliptical jets at all nozzle pressure ratios (NPRs). Core length is reduced to as much as 70% in the elliptical jet and 84% in the case of the circular